Maternal and Fetal Outcomes of Adolescent Pregnancies at Patan Hospital - RC, Laxmi; Baral, Reetu; Shrestha, R; Gurung, P; Lama, S (Nepal Journal of Obstetrics and Gynaecology, 2016)
Aims: This study aims to review obstetric and neonatal outcome and risk factors in adolescent pregnant women and to compare perinatal outcomes with the adult group. Methods: This is a retrospective comparative study in between primiparous pregnant teenager women aged 15-19 years and 20-24 years from April 2012 to April 2013 in Patan Hospital Lalitpur, Nepal. The data was retrieved from the hospital records. Frequency of prenatal care, perinatal outcome (newborn’s weight and gestational age at delivery), mode of delivery and maternal complications if any were recorded. Results: Neonates with normal birth weight (>2.5-4 kg) was seen in 70% (n=248) of the adolescent age group and 85% (n=1797) of adult age group. Neonates with low birth weight (<2.5 kg) was significantly higher in the adolescent age group with 29% (n=102) than the adult age group with only 13% (n=287). The occurrence of premature rupture of membrane and preterm premature rupture of membrane also show statistically significant association (Chi-square test p-value 0.000) on mother’s age having 18% and 2% respectively in adolescent pregnancy. Conclusions: There was significant association of neonatal complications like still birth, fetal distress, and meconium aspiration with the adolescent pregnancy. There was no significant association between neonatal death and age of mother.